Ball Lightning as a Port to a Parallel Space - Sturrock, Peter (Journal of Scientific Exploration, 2017)
Barry1, Singer2, Stenhoff3 have prepared detailed accounts of the curious properties of ball lightning. Current theories, based on present-day physics, fall into two categories: one in which energy is stored in the ball-lightning, and the other in which energy is fed into the ball-lighting from some external source. None of these theories is considered successful by these authors. Recent developments in physics and astrophysics have led to the concept of parallel worlds4. We suggest that this concept may lead to a successful theory of ball lightning.